2022
DOI: 10.1021/jacs.2c08664
|View full text |Cite
|
Sign up to set email alerts
|

Dipole-Modulated Charge Transport through PNP-Type Single-Molecule Junctions

Abstract: The PNP structure realized by energy band engineering is widely used in various electronic and optoelectronic devices. In this work, we succeed in constructing a PNP-type single-molecule junction and explore the intrinsic characteristics of the PNP structure at the single-molecule level. A back-to-back azulene molecule is designed with opposite ∼1.7 D dipole moments to create PNP-type single-molecule junctions. In combination with theoretical and experimental studies, it is found that the intrinsic dipole can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This may be due to the fact that the opposite dipole moments between the donor and bilateral acceptors could generate double barriers along the charge‐transport channel of the A–D–A junction with –CN anchoring sites, which suppress the bias‐dependent charge transport. [ 29 ] All these support that the high conductance state should originate from the −S anchoring way, which becomes feasible after proton bonding and conformation inversion. It is worth mentioning that the TVS characteristics of protonated A–D–A is closer to that of A–D–A without protonation, whose absolute V trans value is also at 0.6 V–0.7 V (Figure 4g).…”
Section: Resultsmentioning
confidence: 83%
“…This may be due to the fact that the opposite dipole moments between the donor and bilateral acceptors could generate double barriers along the charge‐transport channel of the A–D–A junction with –CN anchoring sites, which suppress the bias‐dependent charge transport. [ 29 ] All these support that the high conductance state should originate from the −S anchoring way, which becomes feasible after proton bonding and conformation inversion. It is worth mentioning that the TVS characteristics of protonated A–D–A is closer to that of A–D–A without protonation, whose absolute V trans value is also at 0.6 V–0.7 V (Figure 4g).…”
Section: Resultsmentioning
confidence: 83%
“…Figure S22 reveals that the addition of BQ, IPA, and citric acid did not alter the reduction rate of Cr 6+ . However, the introduction of K 2 S 2 O 8 significantly decreased the Cr 6+ reduction rates, suggesting that photogenerated electrons are the primary active species responsible for Cr 6+ reduction. , Furthermore, the enhanced photoelectrocatalytic performance of the nanocomposite could be attributed to the formation of a p–n–p heterojunction between a p-type H 2 TPP organic moiety and a p–n type β-Bi 2 O 3 –Bi 2 WO 6 nanocomposite, and the schematic representation of the probable energy band structure is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Azulene and its derivatives exhibit unique redox activity resulting from an asymmetric electronic distribution between the electron-rich five-membered ring and the electron-deficient seven-membered ring, making them promising materials for electronic devices. Recently, studies have shown that electropositive or postprotonation monomers can migrate to the cathode and achieve cathodic polycondensation under an electric field. , As a result, we were inspired to rationally design an electropositive azulene-based monomer to prepare an ionic redox-active memristive film. However, the lack of sufficient knowledge of cathodic electropolymerization poses significant challenges in developing a high-quality ionic memristive film and exploring the interfacial polymerization process at the cathode.…”
Section: Introductionmentioning
confidence: 99%